Photodynamic Therapy As an Adjuvant Therapy for Local-Partial Remission of Nasopharyngeal Carcinoma After Standard Therapy in Sardjito Hospital Yogyakarta A Five-Year-Overall Survival Rate Analysis Study - Bambang Hariwiyanto; Sagung Rai Indrasari; Camelia Herdini; Tan IB (MEDIA MEDIKA INDONESIANA, 2012)
Background: The foremost problems of nasopharyngeal carcinoma (NPC) management are high loco-regional remission, local recurrence and spreading rate post therapy. Photodynamic therapy (PDT) has been done for treatment of tumors less than 1 cm in size and depth in a very difficult location, where radical excision by surgery was not possible. The aim of this study is determining 5-year-overall survival rate of local-partial remission of NPC after standard therapy followed by additional PDT.Method: The survival study is subjected to the 5 years-overall survival rate of local-partial remission. Photosensitizer (FoscanR) 0,15mg/kgBW was injected to NPC patients and followed by 20 joule/cm2, 642 wave length and 100 watts/cm2 irradiants non thermal laser illumination 96 hours after injection. The PDT result was confirmed with biopsy, CT scan, upper abdominal USG, thoracic radiograph and bone survey for 12 weeks after treatment. Follow up was done every 3 months in first year, continued every 6 months in the second year, and followed once a year. The sample collected from January 2005 to December 2010, and 33 cases met the inclusion and exclusion criterias, but only 20 cases were eligible inclusion criteria. The 5 years-overall survival was defined as the time from diagnosis to death from any cause or last follow up, calculated by Kaplan Meier survival analysis.Results: The 5-year-overall survival rate was 50%.Conclusion: PDT as an additional treatment for small local-partial remission in NPC post treatment is an alternative therapy to improve the treatment outcome and survival rate.Keywords: NPC, PDT, 5-year-survival rate ABSTRAK Photodynamic therapy sebagai terapi ajuvan karsinoma nasofaring remisi lokal-parsial setelah terapi standar di RSUP Dr. Sardjito Yogyakarta: Studi analisis angka kehidupan lima tahunLatar belakang: Problem utama terapi standar karsinoma nasofaring (KNF) adalah rendahnya angka keberhasilan terapi, terutama adanya remisi parsial, baik pada tumor primer maupun metastasis. Photodynamic therapy (PDT) telah digunakan untuk pengobatan tumor di superfisial, dengan diameter kurang dari 1 cm, terutama pada tumor yang letaknya tersembunyi dan sulit dioperasi secara radikal. Penelitian ini bertujuan menentukan angka kehidupan 5 tahun pada penderita KNF dengan remisi parsial pada tumorprimernya, setelah diterapi secara standar dan dilakukan PDT sebagai terapi tambahan.Metode: Studi analisis kesintasan terhadap kehidupan 5 tahun penderita KNF yang mengalami remisi lokal-parsial setelah terapi standar dan PDT. Photosensitizer (FoscanR) 0,15mg/kgBW diinjeksikan pada penderita KNF, dan setelah 96 jam, dilanjutkan dengan irradiants non thermal laser illumination sebesar 20 joule/cm2, panjang gelombang 642 dan 100 watts/cm2. Hasil PDT dikonfirmasi dengan biopsi, CT scan, USG abdomen, rontgen thoraks dan bone survey pada 12 minggu setelah terapi. Tahun pertama, dilakukan follow up setiap 3 bulan, di tahun kedua setiap 6 bulan, dan selanjutnya setiap setahun sekali. Sampel didapat dari Januari 2005 sampai Desember 2010, dimana 33 pasien KNF post PDT memenuhi kriteria inklusi dan eksklusi, namun hanya 20 pasien yang memenuhi kriteria inklusi 5-tahun-follow up. Angka kehidupan 5 tahun ditentukan berdasarkan saat diagnosis sampai kematian penderita, atau sampai folllow up terakhir, dihitung dengan analisis kesintasan Kaplan Meier.Hasil: Angka kehidupan keseluruhan selama 5 tahun adalah 50%.Simpulan: PDT sebagai tambahan terapi terhadap KNF yang